1987
DOI: 10.2172/901153
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Operation of Kerr and Hungry Horse Dams on the Reproduction Success of Kokanee in the Flathead River System, 1986 Annual Progress Report.

Abstract: V 'gif3-OL61 'cc-8-L-J sqloda~ ssalEo1d 'ira5-m~ pip razuey{ m-73 ale Pqpa '586Ti-OL6-c KOl3 uramis raAQ peaqw[J aq3 u! paqxq~o3 wuqes aaueyoy 30 a& pie pu) qqfma1 TOJ pqq2 A~min.ns 2 avw xrpuadti~

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…These results are consistent with many studies that have shown that dam operations that produce fluctuating or abnormally high discharges disrupt fluvial processes and modify biological characteristics (Ward and Stanford, ; Cushman, ; Poff et al , ). Our study complements other studies in the Flathead River that have shown that flow regulation has dramatically altered the physical characteristics of the riverine environment and lower trophic levels of the aquatic ecosystem (Stanford, ; Stanford and Hauer, ; Hauer and Stanford, ; Fraley and Graham, ; Fraley and Decker‐Hess, ; Beattie et al , ; Hauer et al , ; Christenson et al , ; Hauer et al , ; Marotz et al , ) by quantifying fish habitat changes in the river.…”
Section: Discussionsupporting
confidence: 63%
“…These results are consistent with many studies that have shown that dam operations that produce fluctuating or abnormally high discharges disrupt fluvial processes and modify biological characteristics (Ward and Stanford, ; Cushman, ; Poff et al , ). Our study complements other studies in the Flathead River that have shown that flow regulation has dramatically altered the physical characteristics of the riverine environment and lower trophic levels of the aquatic ecosystem (Stanford, ; Stanford and Hauer, ; Hauer and Stanford, ; Fraley and Graham, ; Fraley and Decker‐Hess, ; Beattie et al , ; Hauer et al , ; Christenson et al , ; Hauer et al , ; Marotz et al , ) by quantifying fish habitat changes in the river.…”
Section: Discussionsupporting
confidence: 63%
“…Changing water levels resulting from operation of these dams reportedly caused kokanee spawning areas in both the river and along the lakeshore to become dessicated, killing kokanee eggs (Fraley et al 1986, Fraley and Decker-Hess 1987. The kokanee also may have been stressed by intensive annual harvests by anglers, which often removed 50% or more of the adult kokanee population (Beattie et al 1988).…”
Section: Impact On Fishmentioning
confidence: 99%
“…The zooplankton community changed dramatically in Flathead Lake following the appearance of the voracious planktivore, M. relicta (Bukantis 1986, Beattie et al 1988, Spencer et al 1991. Cladocerans are preferred prey for M. relicta (Grossnickle 1982, Nero and Sprules 1986, Cooper and Goldman 1980, and previous Mysis introductions have been linked to disappearance of various Cladoceran species in other lakes including Lake Tahoe and Lake Pend Oreille (Richards et al 1975, Rieman and Falter 1981).…”
Section: Cladoceramentioning
confidence: 99%